Leitura e escrita de jovens em contextos de RPG (ROLEPLAYING GAME) - Vivianete Milla de Freitas (2007)
In this research we aim to analyse and to explain how the written of the teenagers reports itself, what are their motivations to write in the context of RPG, (Role playing Games) and in which aspects it favors or not the use of lecture and writing in severe situations. We are looking for along this assignment to understand the structure of the RPG games and to describe possible situations of lecture that comes out from the game. To analyse and to make clear the teenagers written in the RPG context and to map the preparatory lectures for the achievement of the games. The research is qualitative, ethnography and searches the understanding of the object from direct observation and the analysis of the unique productions from a group of subjects that participate in socio cultural contexts linked to the use of RPG. Our methodology consists in the observation in situations of the game, interview with a group of six young players of RPG, and the analysis of the written production by this young players and the documentary research of the game handbook. Among the mainly theorical references, we used Roger Chartin (1998) which contributes for a better view of the changes in the use of the written, Carla viana Coscarelly (2005) Else Martins Dos Santos (2005) e Luciana Zenha Cordeiro (2001) that allows to understand the social manners, from school and not from school and the interferences in the way of lectures and written which comes from the presence of new technologies. Maria da Graça Costa Val (2004) that offers an instrumental theory to analyse the textual characterists presents in the written productions of the teenagers and Sonia Rodrigues (2005) pioneer in the RPG studies in Brazil. The results indicate that the RPG games presents as a large and diverse field for production of oral and written narratives. The teenagers find many reasons to produce written through literary lectures of RPG and from this lectures produce unique texts under the written way such as individual or collective form. The universe of these teenagers lectures is large, diverse and the motive to these practices of lecture. Mainly those which purpose is the preparation for the game. Finally the written that comes from RPG according to the teenagers, contribute for the expansion of their socio relationships.